Determination of human neutrophil antigen‐1, ‐3, ‐4 and ‐5 allele frequencies in English Caucasoid blood donors using a multiplex fluorescent DNA‐based assay. Issue 1 (9th February 2013) - Cardoso, S. P.; Chong, W.; Lucas, G.; Green, A.; Navarrete, C.
<x xml:space="preserve">Abstract</x> Background and Objectives A number of DNA‐based methods to genotype the alleles coding for HNA have been described, but all require the separate amplification and analysis of each allele. The aim was to develop a DNA‐based method for simultaneous detection of HNA‐1, HNA‐3, HNA‐4 and HNA‐5 alleles. Materials and Methods An allele‐specific primer extension method was used in combination with magnetic beads from Luminex technology. PCR–sequence‐specific primers (SSP) was used to resolve the presence of the HNA‐1b allele in samples assigned by the Luminex bead assay as HNA‐1a/‐1b/‐1c or HNA‐1b/‐1c. HNA allele frequencies were determined in a panel of 140 randomly selected English Caucasoid blood donors. Results HNA allelic types were compared with historical results, and 100% concordance was found. Only eight of the 97 samples used in the validation required additional testing by PCR–SSP. Allele frequencies were determined in the blood donor population as follows: 0·318 for HNA‐1a, 0·668 for HNA‐1b, 0·014 for HNA‐1c, 0·768 for HNA‐3a, 0·232 for HNA‐3b, 0·882 for HNA‐4a, 0·118 for HNA‐4b, 0·736 for HNA‐5a and 0·264 for HNA‐5b. Conclusion A multiplex Luminex bead assay for the simultaneous detection of HNA‐1, HNA‐3, HNA‐4 and HNA‐5 alleles is described that enables rapid typing of donors to support HNA alloimmunized patients who require HNA‐compatible blood products.